A NetCDF version of the two-dimensional energy balance model based on the full multigrid algorithm - Kelin Zhuang; Gerald R. North; Mark J. Stevens (SoftwareX, 2017)
A NetCDF version of the two-dimensional energy balance model based on the full multigrid method in Fortran is introduced for both pedagogical and research purposes. Based on the land–sea–ice distribution, orbital elements, greenhouse gases concentration, and albedo, the code calculates the global seasonal surface temperature. A step-by-step guide with examples is provided for practice. Keywords: Energy balance model, Full multigrid algorithm, Seasonal surface temperature